PENGARUH DAYA TARIK DAN PROMOSI TERHADAP MINAT BELI KONSUMEN - Markiz Yudiawan Yudiawan; Asmanih Asmanih (Sekolah Tinggi Ilmu Ekonomi DR KH EZ Mutaqien, 2022)
UMKM is an abbreviation of the word Micro, Small and Medium Enterprises. The growth of Micro, Small and Medium Enterprises (MSMEs) in Indonesia is increasing every year. According to data from the Ministry of Cooperatives and Small and Medium Enterprises, currently SMEs in the country have reached 60 million. This number is predicted to continue to grow in line with technological advances and the potential for human resources is growing. The high growth of MSMEs provides fresh air for the economy in Indonesia, one of which is by successfully opening many new jobs. The purpose of this research is to determine the effect of attractiveness on consumer buying interest in micro-enterprises around the Cawang sub-district. Micro around Cawang Village research on micro businesses around Cawang Village, with a total population of 218 Micro Business Units / 218 people. With a total sample of 37 people obtained from using the slovin formula with an error rate of 15%. Based on the results of data analysis using the SPSS program, the attractiveness variable obtained a significance value of 0.038 <0.05 and a t-count value of 2.162 > a t-table value of 2.032, then Ho was rejected and Ha1 was accepted. meaning that there is a significant effect of attractiveness on consumer buying interest. The promotion variable gets a significance value of 0.000 <0.05 and a t-count value of 4.146 > a t-table value of 2.032, then Ho is rejected and Ha2 is accepted. meaning that there is a significant influence of promotion on consumer buying interest. Meanwhile, to determine the effect simultaneously obtained a significance value of 0.000 <0.05, and F count 28.803 > F table value of 3.28, this proves that Ho is rejected and Ha3 is accepted. This means that there is a significant effect of price (X1) and promotion (X2) on consumer buying intentions (Y).